EVALUASI DAN PERENCANAAN SALURAN DRAINASE DI JALAN SANGGA BUANA II KOTA PALANGKA RAYA - Agustulusnu Agustulusnu; I Made Kamiana; Raden Harya Saputra (Universitas Lambung Mangkurat, 2019)
The siltation occurs nearly along the drainage channel at Sangga Buana II Street Palangka Raya. The catchment area for rainfall is increasingly dense with both residence and shop buildings so that the recharge area is also getting decreased. These factors are assumed able to cause a bigger flood. This study aims to evaluate the flood potential in the channel and design the dimensions of the channel required if the drainage discharge consists of design-discharge with a 2-year return period and domestic-wastewater discharge. This study is conducted in 2019 by using a survey approach. The flood potential is analyzed based on the comparison between both the drainage capacity and drainage discharge. The channel capacity is analyzed by the Manning method while the drainage discharge is analyzed by the Rational method. The domestic-wastewater discharge is assumed equally to 80% of the total use of clean water. The result of study showed that the channel capacity is smaller than the drainage discharge, and it occurs almost along the drainage channel of Sangga Buana II Street Palangka Raya. It means that the channel has flood potential so that it needs to be re-designed. The channel is designed with an opened-channel type and squared-shape with 0,65 m width and 0,65 m depth. The discharge direction is divided into two directions. The first direction flows to the drainage channel at Batu Suli Street while the second one flows to the drainage channel at Lawu Street. It is needed to build box culvert in the five locations to ensure that the discharge direction can flow to the drainage channel both at Batu Suli Street and Lawu Street.